Analysis of Differentiate Learning with Classroom Action Research to Improve Physics Activities and Outcomes - Trapsilo Prihandono; Agung Supriyono; Ujang Fahmi Abdillah; Sudarti Sudarti (Jurnal Penelitian Pendidikan IPA, 2023)
Differentiated learning is a form of learning that is oriented to the needs of students. This research is a classroom action research which aims to determine the effect of implementing visual, auditory, and kinesthetic (VAK) learning style-based differentiation in the Problem Based Learning (PBL) model on students' physics learning activities and outcomes. The material used is global warming. This research was conducted in class X-2 of State High School 3 Jember for the 2022/2023 Academic Year. The subjects of this study were of 36 students who were divided into three VAK learning style profile categories. This research includes quantitative descriptive research. The research data collection method used a Likert scale learning style questionnaire, activity observation sheets and written tests to obtain students' physics learning outcomes. The design used in this study was the Tagart and Kemmis model cycles and the data obtained was analyzed using classical learning completeness. The results showed that there was an increase in student learning activities by 20.14% and an increase in student physics learning outcomes classically by 25% and the average level of mastery learning was above the minimum completeness criteria with an increase in the average score of 6.06. Based on the results of the study, it can be concluded that the application of the PBL learning model based on VAK learning style differentiation can increase student activity and learning outcomes.